PEMBERDAYAAN MASYARAKAT DESA PAKUHAJI MELALUI PROGRAM KKNT UNTUK PENINGKATAN KESEJAHTERAAN BERKELANJUTAN - Tubagus Akbar; Rana Alifa Haryanto; Dadin Solihin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) – Sekolah Tinggi Agama Islam (STAI) Pelita Nusa Bandung Barat, 2024)
Village empowerment is a strategic step to increase independence, welfare, and community participation in utilizing local potential to achieve sustainable growth. Pakuhaji Village has potential in agriculture, tourism, and entrepreneurship, but is faced with the challenges of poverty, low education levels, access to health, unemployment, limited infrastructure, and lack of access to technology. This research aims to empower Pakuhaji Village through the Thematic Real Work Lecture (KKNT) program which covers seven main areas. The methods used include literature studies, observations, and interviews as the basis for designing the implemented program. The KKNT program includes activities in the fields of tourism, economy, food security, education, technology, religion, and socio-cultural. The activities carried out include posyandu, teaching at school, financial seminars, routine recitations, and competition events. The results of the program show an increase in social awareness and insight of students, as well as motivate the community to work hard, think critically, and develop with enthusiasm.